Effect a Chemical Treatment of Pineapple Leaf Fiber (PALF) for Mechanical Properties as a Reinforced Composite Matrix Polyesters - Fadil Azhar Ekoputra; Sulistijono Sulistijono; Ika Ismail (Institut Teknologi Sepuluh Nopember, 2018)
Application of composite materials as a alternative materials is developed, The most of composite material is polymer matrix composite (PMC), with the polymer as a matrix and the sintetic fiber such as fiberglass and fiber carbon as a reinforced, it can make a materials with intermediete mechanical properties such as strength, hardness and thoughness, between matrix and fiber. Since the synthetic fiber was dangerous for human, so recenly developing natural fiber composite with advantages of natural fiber is more environmentally friendly, and more cheap than synthetic fiber. Otherwise, natural fiber has stong enough when it use at interior automotive parts, such as dashboard. Some cars already use the natural fiber for the interior parts. The natural fiber has a big potential, especially pineapple in Indonesia, the pineapple production at East Kalimantan is 25 344 tonnes in 2014. It means a lot of leaves can be used for the natural fiber. Pineapple leaf fiber (Pineapple Leaf Fiber / PALF) has a pretty good tensile strength of 126 MPa, and Young modulus of 4405 MPa and has a cellulose content About a 70-80% cellulose, cellulose which has a crystalline structure, so it can be good reinforced for composite. The result of this experiment, the optimum value of tensile strength is 29.9648 MPa, at composite PALF – Alcalinitation 40%.